Oil yield and Sterols content in Seeds and Barks of Wild and Domestic Plants Growing in Kahuzi-Biega National Park and surroundings - Pius Mpiana Tshimankinda; Melchias Kazadi Minzangi; Emmanuel Lushombo B.; Justin Kadima N.; Dieudonné Mosibono E; Belesi Katula; Augustin Malumba M. (Revue Congolaise des Sciences et Technologies)
Kahuzi-Biega National Park in the Democratic Republic of the Congo is home to various plants as sources of edible oil for food preparations and medicinal therapy. This study aimed to assess and compare the oil yield and phytosterol content of seeds and barks of eight plants growing in this park and its surroundings. These were Albizia grandibracteata, Hagena abyssinica, Millettia dura, Piptadeniastrum africanum, Prunus africana, Prunus salsii, Sesbania sesban and Tephrosia vogelii. Common procedures for petroleum extraction and gas chromatography were used. The seeds of Prunus salsii contain the highest yield of crude oil (45.8%). Millettia dura and Piptadeniastrum africanum have the highest total sterol content (27-54 mg / g oil). Among the thirteen phytosterols identified, the most abundant are β-sitosterol, stigmasterol, campesterol and 5-avenasterol. The properties of these phytosterols support the traditional use of these plants as sources of oils for cooking and health issues.